2019
DOI: 10.1016/j.cub.2019.09.062
|View full text |Cite
|
Sign up to set email alerts
|

Evolution: Adapting to a Warming World

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…On the basis of rapid global warming projected in the future (Diffenbaugh & Field, 2013), with stronger effects toward higher latitudes in the Northern Hemisphere (IPCC, 2001;Parmesan, 2007;Shukla et al, 2019), there is a high risk that long-distance migrants, especially in their northernmost breeding range, at some point will be unable to fully adjust breeding time in response to climate change. The reduced breeding success in Swedish pied flycatchers at southern and mid-latitudes during warm springs reported in our study could thus be expected to also occur in more northern breeding birds with continued climate change and indicates a fate that could be true for several long-distance migratory species (Radchuk et al, 2019;Visser, 2019).…”
Section: Effects On Breeding Successmentioning
confidence: 72%
“…On the basis of rapid global warming projected in the future (Diffenbaugh & Field, 2013), with stronger effects toward higher latitudes in the Northern Hemisphere (IPCC, 2001;Parmesan, 2007;Shukla et al, 2019), there is a high risk that long-distance migrants, especially in their northernmost breeding range, at some point will be unable to fully adjust breeding time in response to climate change. The reduced breeding success in Swedish pied flycatchers at southern and mid-latitudes during warm springs reported in our study could thus be expected to also occur in more northern breeding birds with continued climate change and indicates a fate that could be true for several long-distance migratory species (Radchuk et al, 2019;Visser, 2019).…”
Section: Effects On Breeding Successmentioning
confidence: 72%
“…Neuromodulation is important for insect feeding, courtship, aggression, and postmating behaviors [62], and the number of synapses is a major determinant of behavior [63]. Evolutionary pressures induced by temperature play an important role in shaping phenotypic variation between and within species [64,65]. Previous studies have demonstrated that the abundance of many metabolites in P. rapae and warming-induced key biochemical pathways have changed significantly in warming environments [66].…”
Section: Plos Onementioning
confidence: 99%
“…Genome diversity is formed by a balance of mutation, drift, and gene flow contributing to the distribution of diversity across the loci along the chromosomes of individuals in a population. The resulting patterns of variation provide a backdrop for natural selection, enabling adaptation [ 4 , 5 ], and it is generally thought that preserving genetic diversity is required for adaptability: a species that has lost all its reserves of genetic diversity is doomed to extinction [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. In this context, adaptability is generally understood to depend on the existing genetic variation within each species.…”
Section: Introductionmentioning
confidence: 99%